Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru di SMAN 8 Tambun Selatan - Aulya, Rafi Alif; Sinaga, Jhonni; Supriyanto Supriyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the influence of leadership style, work motivation, and work environment on teacher performance at SMAN 8 Tambun Selatan, both partially and simultaneously. The background of this research is based on the crucial role of teachers in improving the quality of education, as well as the observed variations in teacher performance that are presumed to be influenced by school leadership, individual motivation, and the working environment. This research employs a quantitative approach using a survey method. The population consists of all 40 teachers at SMAN 8 Tambun Selatan, and the sampling technique used is total sampling. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results show that: (1) leadership style have a significant effect on teacher performance when tested partially; (2) work motivation has a positive and significant effect on teacher performance; (3) the work environment does not significantly affect teacher performance; and (4) simultaneously, leadership style, work motivation, and work environment significantly influence teacher performance. The findings imply that increasing work motivation is a key factor in enhancing teacher performance, while leadership style and work environment require further optimization to comprehensively support performance.